Research instruments in social gerontology. - Mangen, David J.; Peterson, Warren A., 1922- (Clinical & Social Psychology., 1982)
The increasing number of older people in the United States has served to focus attention upon the processes of aging and the effectiveness of social programs for the elderly. In order to plan effective programs, accurate social measures are necessary. Now, more than ever before, researchers require conceptually explicit instruments designed to assess individual and social behaviors, attitudes, and traits in the elderly population. This is the first in a three-volume series designed to serve the needs of researchers, evaluators, and clinicians in assessing the instruments used in the field of a.